ANALISIS SIX SIGMA DMAIC DALAM MENGURANGI DEFECT STRUKTUR ATAP PIPA BAJA PADA PROYEK PERLUASAN TERMINAL BANDARA INTERNASIONAL LOMBOK - Adiasa, Iksan; Andi Muhammad Fiqri Achmad; Nur Khaerani Busri; Ridho Rabbani (Hexagon Jurnal Teknik dan Sains, 2024)
Quality is an important indicator of a product. PT. XYZ is a company engaged in the field of construction services, Engineering Procurement Construction (EPC), and Investment which is currently expanding its terminal and facilities at Lombok International Airport (BIL). Results Based on the inspection, various Defects were found in the steel such as cracked welded joints, peeling steel paint, thin paint thickness. This will have an impact if the steel roof truss structure is Defective, it will endanger the collapse of the building and the safety of visitors at BIL. Based on this, an analysis is carried out on the work of the steel pipe roof truss structure that occurs in the terminal expansion project and its supporting facilities so that recommendations for improvement can be made. This research was conducted using the Six Sigma method. The result of the research is that the main factor that causes failure is the steel pipe being stepped on during the installation of electrical installations. The proposed improvement to overcome these Defects is to provide ongoing counseling and training programs on worker compliance in carrying out work by the Standard Operating Procedures available in all work processes. It is hoped that by conducting this research, the company can better maintain quality so that the risk of building collapse and safety from incidents cannot be avoided.